Webinar Summary Report: Targeting Tools: Providing climate risk maps to the livestock community - Kimani, Lucy (International Center for Tropical Agriculture, 2023)
On Thursday, June 22, 2023, the One CGIAR initiative on Livestock and Climate conducted a webinar on Microsoft Teams with the purpose of creating awareness about using the Targeting Tools as way to provide climate risk layers to the livestock community. The primary focus was to demonstrate the capabilities of the Targeting Tools, guide attendees in navigating the web application, and provide information on the available datasets.